Plant heat shock protein 90 as carrier-adjuvant for immunization against a reporter antigen - Corigliano, Mariana Georgina (2013)
Here, we evaluated the modulation of the immune response induced by Hsp90 of Nicotiana benthami-ana (NbHsp90.3) against the Maltose Binding Protein (MBP) as a reporter antigen. Equimolar quantitiesof recombinant proteins were administered in mice as follows: MBP alone (MBP group), a mixture ofMBP and rNbHsp90.3 (MBP + rNbHsp90.3 group) and the fusion of MBP to rNbHsp90.3 (MBP-rNbHsp90.3group). The covalent linkage between NbHsp90.3 and MBP to bring a fusion protein was essential toinduce the strong specific antibody response with predominance of IgG2a. Eighty-four days after the firstimmunization, splenocyte proliferation from MBP-rNbHsp90.3-immunized mice was consistently higherthan that from MBP and MBP + rNbHsp90.3 groups. In addition, splenocytes from MBP-rNbHsp90.3 immu-nized mice produced higher levels of IFN- than controls. Finally, both formulations with rNbHsp90.3significantly enhanced the MHC class I expression levels, but only rNbHsp90.3 covalent bound to MBPinduced a specific cellular immune response against MBP measured as increased percentage of CD8+Tcells. Taken together, these results suggest that plant HSP90s could be incorporated as adjuvants in vac-cines that require the generation of a Th1 response along with a CD8 cytotoxic cell response to conferimmunity.